Interaksi antara Ayah dan Anak pada Konsep Ibn dalam Alquran dan Implikasinya terhadap Pembelajaran PAI di Sekolah - Deni Tisnawan (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2017)
In this research analyzed some verses pertaining to the word bunayya, which is defined as an addressing term for a child that is full of affection. In Islam, educating a child is very important; therefore, parents are obligated to educate and direct their children to the right path. The research adopted descriptive method with qualitative approach. The technique use for data collection was literature study. In this research, the researcher is the main instrument. Based on the findings, it can be inferred that affection is the primary foundation in education. As the education given is laid on the basis of affection, no matter how hard the commands, prohibitions, and even reprimands are, a child will more easily accept them because they are given by the father with full of affection. Subsequently, the implication of the findings for the teaching and learning of Islamic education in schools is that in the inculcation of the values of affection, an educator should educate and teach knowledge to his or her students with full of affection.